The role of short-chain fatty acids in inflammatory skin diseases - Xiao, Xianjun; Hu, Xiaoshen; Yao, Junpeng; Cao, Wei; Zou, Zihao; Wang, Lu; Qin, Haiyan; Zhong, Dongling; Li, Yuxi; Xue, Peiwen; Jin, Rongjiang; Li, Ying; et al. (Frontiers in Microbiology, 2023)
Short-chain fatty acids (SCFAs) are metabolites of gut microbes that can modulate the host inflammatory response, and contribute to health and homeostasis. Since the introduction of the gut-skin axis concept, the link between SCFAs and inflammatory skin diseases has received considerable attention. In this review, we have summarized the literature on the role of SCFAs in skin inflammation, and the correlation between SCFAs and inflammatory skin diseases, especially atopic dermatitis, urticaria, and psoriasis. Studies show that SCFAs are signaling factors in the gut-skin axis and can alleviate skin inflammation. The information presented in this review provides new insights into the molecular mechanisms driving gut-skin axis regulation, along with possible pathways that can be targeted for the treatment and prevention of inflammatory skin diseases.